Financial Distress Analysis Of Hotel Companies Listed On The Indonesia Stock Exchange During The Covid-19 Pandemic - Rudy Syafariansyah Dachlan (Jurnal Mantik, 2022)
Financial Distress is a situation that portrays the organization's financial condition, whether the organization is in a tough situation, emergency or undesirable that happened before the organization failed. This study aims to analyze Financial Distress in hotel companies registered on The Stock Exchange of Indonesia during the Covid-19 pandemic for the 2020-2021 utilizing the Altman's Z-Score modified model. The sampling of this research is 19 financial statements of hospitality companies in the period 2020-2021. The Outcomes showed that during the Covid-19 Pandemic from 2020 to 2021, of the 19 companies that were the sample of this study, 10 companies (53%) were in the Distress Area and the Gray Area. The remaining 9 companies (47%) are in the Non Distress Area. This study concludes that the COVID-19 pandemic for the 2020-2021 period has had quite an impact on financial distress for hotel companies filed on the Indonesia Stock Exchange.